Silk scaffolds with tunable mechanical capability for cell differentiation. (1st July 2015) - Bai, Shumeng; Han, Hongyan; Huang, Xiaowei; Xu, Weian; Kaplan, David L.; Zhu, Hesun; Lu, Qiang
Graphical abstract: Abstract: Bombyx mori silk fibroin is a promising biomaterial for tissue regeneration and is usually considered an "inert" material with respect to actively regulating cell differentiation due to few specific cell signaling peptide domains in the primary sequence and the generally stiffer mechanical properties due to crystalline content formed in processing. In the present study, silk fibroin porous 3D scaffolds with nanostructures and tunable stiffness were generated via a silk fibroin nanofiber-assisted lyophilization process. The silk fibroin nanofibers with high β-sheet content were added into the silk fibroin solutions to modulate the self-assembly, and to directly induce water-insoluble scaffold formation after lyophilization. Unlike previously reported silk fibroin scaffold formation processes, these new scaffolds had lower overall β-sheet content and softer mechanical properties for improved cell compatibility. The scaffold stiffness could be further tuned to match soft tissue mechanical properties, which resulted in different differentiation outcomes with rat bone marrow-derived mesenchymal stem cells toward myogenic and endothelial cells, respectively. Therefore, these silk fibroin scaffolds regulate cell differentiation outcomes due to their mechanical features.